How grounded can facilitate research studies in context of agile software development. - Gandomani, Taghi Javdani; Zulzalil, Hazura; Abdul Ghani, Abdul Azim; Md Sultan, Abu Bakar; Sharif, Khaironi Yatim (Publications International, Lahore, 2013)
Agile methods are increasingly used in software development. These methods are people oriented and almost all issues and challenges in using them are associated to people and their behaviours. While many challenges should be studied in Agile environments, using appropriate research methodology is so critical and affects such studies strongly. This article shows that Grounded Theory as a qualitative research methodology can be used in conducting studies in Agile context. This article presents applicability of Grounded Theory for developing inductive substantive theories in Agile environments based on the real data. There are several reasons for using Grounded Theory in Agile context which all of them go back to the nature of Agile approach and Grounded Theory characteristics.